(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2024)
The preservation of national parks has emerged as a significant component of Indonesia’s climate mitigation efforts, primarily due to its substantial carbon stocks. However, little is known about the potential carbon stored in deadwoods within these areas. This study aims to estimate fallen deadwood carbon stocks in four national parks in Indonesia. The results show that the density of deadwood in study areas ranges from 0.26 – 0.79 g cm-3. Deadwood volume varies between 247.37 – 388.50 cm3. Bukit Tigapuluh National Park has the highest fallen deadwood biomass and carbon stock, accounting for 261.35 and 122.83 tons ha-1, respectively, followed by Sebangau National Park (187.41 and 88.08 tons ha-1), Kutai National Park (139.91 and 65.76 tons ha-1) and Lore Lindu National Park (87.90 and 41.32 tons ha-1). This study also found that large deadwood with diameters of >7.5 cm contributes to more than 80% of the total deadwood carbon stock. Understanding the carbon stock stored in deadwood within national park areas is crucial for refining estimates of potential avoided greenhouse gas emissions resulting from the conservation of national park forests.